Synthesis Anodised Al Oxide for DNA Detection - Nazurah Razlee (School of Materials Engineering, Universiti Malaysia Perlis, 2017)
To optimize the anodizing parameters which concentration, voltage, and time by using Taguchi method so that the polarization resistance can be improved to the highest.To investigate the feasibility of anodized aluminum oxide for detecting DNA